Pengaruh Gaya Kepemimpinan, Komitmen Organisasi Dan Kompensasi Terhadap Kepuasan Kerja: (Studi Kasus: Bank Nagari Cabang Simpang Empat Pasaman Barat) - Yudi Farwis; Khairil Aswan (Pusat Riset dan Inovasi Nasional, 2023)
The scope of human resource management in general discusses matters relating to humans, including employee job satisfaction. Employee satisfaction is a factor that is considered important, because it can affect the organization's overall fraud. The satisfaction felt by employees at work is an indication that employees have feelings of pleasure in carrying out work assignments. Job satisfaction is also a positive employee attitude towards various situations in the workplace. This study aims to look at the influence of leadership style, organizational commitment and feelings on job satisfaction in Bank Nagari Simpang Empat Pasaman Barat employees. Sampling using a saturated sample that is as many as 56 employees. The results obtained are motivation and content on employee performance that affect employee performance at Bank Nagari Simpang Empat Pasaman Barat.